PRODUCTIVITY AND ESTIMATED BREEDING VALUE OF THE DAIRY CATTLE GENE POOL IN THE REPUBLIC OF KAZAKHSTAN - Baimukanov, D. A.; Abugaliyev, S. K.; Seidaliyev, N. B.; Chindaliyev, A. E.; Dalibayev, E. K.; Zhamalov, B. S.; Muka, Sh. B. (My University, 2019)
The average milk yield of the studied herds per 1 cow was 5300 +/- 30 kg of milk, with a mass fraction of fat of 3.74 +/- 0.02%, the mass fraction of protein of 3.16 +/- 0.01%, with a content of 324.7 +/- 23.8 thous. of somatic cells. The most productive were the cows of the Holstein breed, their productivity over the Alatau breed was 694 kg (P 0.99), over the black-and-motley breed it was1446 kg (P 0.999), over the Simmental breed it was 1982 kg (P 0.999), over the red steppe-2038 kg (P0.999), no significant difference was found in the content of fat and protein of cow. Somatic cells were within normal limits. When studying the dynamics of milk yields according to lactation, it is established that the milk productivity of the Alatau breed is characterized by growth (4844... 5679... 5458 kg) by the second-third lactation and gradual decrease (4716... 4017 kg) by the fifth. On average, for all lactations, cows of this breed brought 5123 +/- 275.4 kg. The dairy productivity of Holstein cows is increased by the fifth lactation, without recessions. On average, for cows of black and motley breed for all lactations, the milk yield was 4671 +/- 190 kg. Dynamics of milk yield of the Simmental breed increases from the first to the second lactation (3917... 4035 kg), in the third it decreases (4035... 3334 kg), from the fourth to the sixth lactation the sequence increases.Средний удой исследуемого стада на 1 корову составил 5300 +/- 30 кг молока, с массовой долей жира 3,74 +/- 0,02%, массовой долей протеина 3,16 +/- 0,01%, с массовой долей жира 3,16 +/- 0,01%. содержание 324,7 +/- 23,8 тыс. соматических клеток. Наиболее продуктивными оказались коровы голштинской породы, их продуктивность по породе Алатау составила 694 кг (P 0,99), по черно-пестрой породе - 1446 кг (P 0,999), по симментальской породе - 1982 г. кг (P 0,999), над красной степью - 2038 кг (P 0,999) существенной разницы в содержании жира и белка коровы не обнаружено. Соматические клетки были в пределах нормы. При изучении динамики удоев по лактации установлено, что молочная продуктивность алатауской породы характеризуется ростом (4844 ... 5679 ... 5458 кг) ко второй-трети лактации и постепенным снижением (4716. . 4017 кг) пятым. В среднем за все лактации коровы этой породы принесли 5123 +/- 275,4 кг. К пятой лактации молочная продуктивность коров голштинской породы увеличивается без спадов. В среднем у коров черно-пестрой породы за все лактации удой составил 4671 +/- 190 кг. Динамика удоя симментальской породы увеличивается от первой ко второй лактации (3917 ... 4035 кг), в третью она снижается (4035 ... 3334 кг), от четвертой к шестой лактации последовательность увеличивается.
BULLETIN OF THE NATIONAL ACADEMY OF SCIENCES OF THE REPUBLIC OF KAZAKHSTAN. - 2019.
Keywords: импакт-фактор 2019; web of science; кларивате аналитикс; томсон; зарубежные авторы; научный журнал; отечественное издание; периодическое издание; молочное скотоводство; голштинская порода скота; алатаусая порода скота